synthesis and evaluation of dimethyl tin 4-cyclohexyl thiosemicarbazone as a novel antitumor age - Sen, A.; Chaudhuri, T.K. (Experimental Oncology, 2009)
Aim: To develop a rationally designed new organotin compound namely dimethyl tin 4-cyclohexyl thiosemicarbazone (D4-t) and evaluate its putative antitumor activity. Methods: Starting from 4-cyclohexyl thiosemicarbazone, a three step synthetic procedure was followed to obtain the title compound. In vivo lymphocyte activation property of the compound at three different doses was assayed by measuring the blastogenesis. Concanavalin A (ConA) was used as standard mitogen for murine T cells stimulation in vivo. Also, the synthesis of DNA by the activated lymphocytes was measured after injecting the D4-t. The lymphocyte activation property and antitumor efficacy of D4-twere assessed inSarcoma-180 (S-180) bearing mice. The organization of lymphoid cells was studied in the histological preparations ofspleen and mesenteric lymph node. Tumor neutralization assay (Winn assay) was conducted to examine whether immune responses were associated with the manifestation of antitumor efficacies of this compound in S-180 in vivo. The DNA synthesis inhibitory effect of the compound in S-180 cells was studied in vitro, and was found significant (P < 0.001). Results: Different doses of the new compound caused differential response of blastogenesis and DNA synthesis. In comparison to ConA, the title compound showed a good number of blast cells at its optimum dose of 5 mg/kg. It caused maximum synthesis of DNA by the lymphoid cells. In histological preparations, the gradual transformation of lymphocytes into blasts was observed without any visible toxicity. Winn assay revealed that 5 mg/kg of D4-t was able to reduce tumor mass without severe toxicity. This organotin compound also inhibits the synthesis of DNA in S-180 tumor cells in comparison to Platin10 and ConA. Conclusion: The title compound has the lymphocyte activation property and stimulates immune response of the lymphoid cells, which in turn express the antitumor activity without any significant toxicity. Results indicate promising therapeutic potential of D4-t.